Les sans-abris des quais d’Austerlitz - Emmanuel Fillon; Claire Hemery; Guillaume Lannerée (EchoGéo)
The homeless' spatial practices are not well-known: that's why we tried, relying on several interviews, to study their spatiality which is similar to a perpetual fight. Forced to move by frequent explusions, yet their way of life is sedentary. This sedentarity has been increased by the use of tents which contribute to the homeless visibility in society. Through restoration of their visibility and of their spatiality, the homeless escape for a while from this "nowhere" where one easily banishes them.